Authorship and Greek song : authority, authenticity, and performance - Bakker, Egbert J. (Mnemosyne, Supplements, 2017)
Authorship and Greek Song is a collection of papers dealing with various aspects of authorship in the song culture of Ancient Greece. In this cultural context the idea of the poet as author of his poems is complicated by the fact that poetry in archaic Greece circulated as songs performed for a variety of audiences, both local and "global" (Panhellenic). The volume's chapters discuss questions about the importance of the singers/performers; the nature of the performance occasion; the status of the poet; the authority of the poet/author and/or that of the performer; and the issues of authenticity arising when poems are composed under a given poet's name. The volume offers discussions of major authors such as Pindar, Sappho, and Theognis.